KAJIAN KEANGGOTAAN INDONESIA DALAM ISO/TC BIDANG INDUSTRI LOGAM, MESIN DAN ALAT ANGKUT - Prihadi Waluyo; Muti Sophira Hilman (JURNAL STANDARDISASI, 2006)
In facing of the industrialization era after crisis term claim to us to be always keeping pace with the movement which could happen in the world including in the international standard. Study on the level of membership ofIndonesia participation in the international standardization organization ISO/TC in the fields of metals, machines and transportation equipments industry will be one of the significant input for decision makers in phasing those situations. Technical Commmittee (TC) selection criteria use four factors involve the need of consumers, producers, government and availibility of resources, and six sub factors include import value, export value, standardization cooperation, products, natural resources and human resources. Sub committee (SC) selection criteria are derived from TC concerned. From this study, through weighting criteria approach, ten TC/ISO were chosen which involve metal products, machinery and road vehicle and suggestion for Indonesia membership based on criteria assessment for SC is P-member for 2 SC (metal product), 8 SC (machinery) and 23 SC (road vehicle), O member for 4 SC (metal product), 2 SC (machinery) and 10 SC and non member for 2 SC (machinery)and 12 SC (road vehicle).